A 2D Ultrathin Nanopatterned Interlayer to Suppress Lithium Dendrite Growth in High‐Energy Lithium‐Metal Anodes. Issue 34 (19th July 2022) - Han, Kyu Hyo; Seok, Jae Young; Kim, In Ho; Woo, Kyoohee; Kim, Jang Hwan; Yang, Geon Gug; Choi, Hee Jae; Kwon, Sin; Jung, Edwin Ino; Kim, Sang Ouk
Abstract: A novel strategy for robust and ultrathin (<1 µm) multilayered protective structures to address uncontrolled Lithium (Li) dendrite growth at Li‐metal battery anodes is reported. Synergetic interaction among Ag nanoparticles (Ag NPs), reduced graphene oxide (rGO) films, and self‐assembled block‐copolymer (BCP) layers enables effective suppression of dendritic Li growth. While Ag NP layer confines the growth of Li metal underneath the rGO layer, BCP layer facilitates the fast and uniformly distributed flux of Li‐ion transport and mechanically supports the rGO layer. Notably, highly aligned nanochannels with ≈15 nm diameter and ≈600 nm length scale interpenetrating within the BCP layer offer reversible well‐defined pathways for Li‐ion transport. Dramatic stress relaxation with the multilayered structure is confirmed via structural simulation considering the mechanical stress induced by filamentary‐growth of Li metal. Li‐metal anodes modified with the protective layer well‐maintain stable reaction interfaces with limited solid‐electrolyte interphase formation, yielding outstanding cycling stability and enhanced rate capability, as demonstrated by the full‐cells paired with high‐loading of LiFePO4 cathodes. The idealized design of multilayer protective layer provides significant insight for advanced Li‐metal anodes. Abstract : An ultrathin (<1 µm) multilayered protective (composed of lithiophilic seeds, 2D blocking layer, and vertically porous membrane) is strategically designed for tackling the chronic issue of dendritic growth of lithium (Li). The synergetic interactions between the layers enhance mechanical robustness and facilitate fast and homogenized Li‐ion flux, which result in smooth and stabilized Li growth and outstanding cycling stability.